Жизнь Арсеньева - Бунин Иван Алексеевич (Бриллиантовая коллекция, 2006)
Экземпляры: ЦБ (20220329ԁ) / Инвентарный номер: 62886 / Цена: 50.00 / Сис.шифр: Р1 / Авт.знак: Б 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1